The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1016/0008-6223(72)90011-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion coefficients of graphite crystals

Abstract: Graphite crystal expansions were derived as a function of temperature using the theoretical relationships of ~i ley(' ); the resultant 1 equations provide reasonable f i t s t o the measured l a t t i c e expansion . I data over the temperature range 300' t o 3000°K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 17 publications
7
46
2
Order By: Relevance
“…Below room temperature, we find good agreement with the experimental in-plane coefficients of thermal expansion, 16,80 not surprising considering the agreement in the specific heat at this temperature observed previously. From 300 to 100 K, the X6 potential overestimates the thermal expansion coefficient by 40%, although convergence is observed at higher temperatures.…”
Section: Lattice Parameters and Thermal Expansionsupporting
confidence: 91%
“…Below room temperature, we find good agreement with the experimental in-plane coefficients of thermal expansion, 16,80 not surprising considering the agreement in the specific heat at this temperature observed previously. From 300 to 100 K, the X6 potential overestimates the thermal expansion coefficient by 40%, although convergence is observed at higher temperatures.…”
Section: Lattice Parameters and Thermal Expansionsupporting
confidence: 91%
“…This leads to a ''hexagonal'' lattice constant in the (111) plane of 0.2528 nm for nickel and 0.2533 nm for c-Ni(Al). Comparison of these values with the lattice constant of the graphite basal plane, which has a value of 0.24608 nm at 650°C [38], hints at a smaller misfit for pure nickel. While the changes in lattice parameters are only small, the solubility of carbon increases significantly from 0.01 wt% for pure nickel [39] to 1.1 wt% for Ni 2.5Al at 700°C: Schuster et al [40] reported a solubility of at least 5 at.% C in a 90 at.% Ni and 5 at.% Al mixture at 700°C.…”
Section: Dusting Kinetics and Morphologiesmentioning
confidence: 86%
“…Before performing AIMD simulations DFT simulations on the unit-cell were performed to predict the 0 K lattice parameters, summarized in Tables 1 and 2 for beryllium and graphite respectively. Subsequently, the lattice parameters of the supercell at each temperature were determined from these 0 K parameters using the experimental thermal expansion coefficients [14,15]. Initially the supercell was equilibrated using AIMD at the simulation temperature for 1000 time-steps of 1fs using a canonical thermodynamic ensemble (NVT).…”
Section: Calculation Of Phonon Density Of Statesmentioning
confidence: 99%